Fervor Forever. (1st June 2022) - Brossard, Nicole; Davis, Christine
A conversation Nicole Brossard and artist Christine Davis about their collaboration Typhon Dru (1990), and Brossard's relationship to archives (her own and historical) as well as queerness, desire, and the theme of devotion.